A high-efficiency self-powered wireless sensor node for monitoring concerning vibratory events. (14th August 2017) - Xu, Dacheng; Li, Suiqiong; Li, Mengyang; Xie, Danpeng; Dong, Chuan; Li, Xinxin
Abstract: This paper presents a self-powered wireless alarming sensor node (SWASN), which was designed to monitor the occurrence of concerning vibratory events. The major components of the sensor node include a vibration-threshold-triggered energy harvester (VTTEH) that powers the sensor node, a dual threshold voltage control circuit (DTVCC) for power management and a radio frequency (RF) signal transmitting module. The VTTEH generates significant electric energy only when the input vibration reaches certain amplitude. Thus, the VTTEH serves as both the power source and the vibration-event-sensing element for the sensor node. The DTVCC was specifically designed to utilize the limited power supply from the VTTEH to operate the sensor node. Constructed with only voltage detectors and MOSFETs, the DTVCC achieved low power consumption, which was 65% lower compared with the power management circuit designed in our previous work. Meanwhile, a RF transmit circuit was constructed based on the commercially available CC1110-F32 wireless transceiver chip and a compact planar antenna was designed to improve the signal transmission distance. The sensor node was fabricated and was characterized both in the laboratory and in the field. Experimental results showed that the SWASN could automatically send out alarming signals when the simulated concerning event occurred. The waiting time between two consecutive transmission periods is less than 125 s and the transmission distance can reach 1.31 km. The SWASN will have broad applications in field surveillances.